Microtubule-based peroxisome movement - Rapp, Stephan; Saffrich, Rainer; Anton, Markus; Jäkle, Ursula; Ansorge, Wilhelm; Gorgas, Karin; Just, Wilhelm W. (Journal of cell science, 1996)
The association of peroxisomes with cytoskeletal structures was investigated both by electron microscopy and by kinetic analysis of peroxisome movement. The morphological studies indicated distinct interactions of peroxisomes with microtubules and frequently revealed multiple contact sites. The kinetic approach utilised microinjection and import of fluorescein-labeled luciferase in order to mark and track peroxisomes in vivo. Peroxisomal motility was analysed by time-lapse imaging and fluorescence microscopy. According to their movement peroxisomes were classified into two groups. Group 1 peroxisomes comprising the majority of organelles at 37°C moved slowly with an average velocity of 0.024±0.012 µm/second whereas the movement of group 2 peroxisomes, 10-15% of the total population, was saltatory exhibiting an average velocity of 0.26±0.17 µm/second with maximal values of more than 2 µm/second. Saltations were completely abolished by the microtubule-depolymerising drug nocodazole and were slightly reduced by about 25% by cytochalasin D which disrupts the actin microfilament system. Double fluorescence labeling of both peroxisomes and microtubules revealed peroxisome saltations linked to distinct microtubule tracks. Cellular depletion of endogenous levels of NTPs as well as the use of 5’-adenylylimidodiphosphate, a nonhydrolysable ATP analog, applied to a permeabilised cell preparation both completely blocked peroxisomal movement. These data suggest an ATPase dependent, microtubule-based mechanism of peroxisome movement. Both the intact and the permeabilised cell system presented in this paper for the first time allow kinetic measurements on peroxisomal motility and thus will be extremely helpful in the biochemical characterisation of the motor proteins involved.
Gesehen am 22.04.2025